Basic Cell Culture Protocols - Pollard, Jeffrey W.; Walker, John M.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1997)
Now completely revised and updated from the original, much-acclaimed and bestselling first edition, Basic Cell Culture Protocols, 2nd ed. offers today's most comprehensive collection of easy-to-follow, cutting-edge protocols for the culture of a wide range of animal cells. Its distinguished contributors-often the perfectors of the detailed techniques being described-provide explicit, step-by-step instructions, along with extensive notes and tips that allow both experts and beginners to successfully achieve their desired results. Topics range from basic culture methodology to strategies for culturing previously uncultured cell types and hard-to-culture differentiated cells. Methods are also provided for the analysis of living cells by FACS, video microscopy, and confocal microscopy. Basic Cell Culture Protocols, 2nd ed. will surely follow in the footsteps of the first edition and, in the words of the reviewers, prove a still more "clear, easy-to-use well-sourced, and precise" work that belongs "in every cell culture laboratory.".
Basic Cell Culture -- Establishment, Maintenance, and Cloning of Human Dermal Fibroblasts -- Aging of Cultured Human Skin Fibroblasts -- Ex Vivo Maintenance of Differentiated Mammalian Cells -- Scale-Up of Suspension and Anchorage-Dependent Animal Cells -- Hollow-Fiber Cell Culture -- Separation and Maintenance of Primary T- and B-Lymphocytes -- Human Pilosebaceous Culture -- Keratinocyte Culture -- Tissue Culture of Skeletal Muscle -- Isolation of Rat Liver Hepatocytes -- Primary Kidney Cells -- Human Thyroid Epithelial Cells -- Derivation and Maintenance of Embryonic Stem Cell Cultures -- Culture of Cells From Human Tumors of the Nervous System on an Extracellular Matrix Derived from Bovine Corneal Endothelial Cells -- Culturing Primitive Hemopoietic Cells -- Collagen Gel Culture of the Human Hematopoietic Progenitors CFU-GM, CFU-E, and BFU-E -- Long-Term B-Lymphoid Cultures from Murine Bone Marrow Establishment and Cloning by Using Stromal Cell Line AC 6.21 -- Human Long-Term Bone Marrow Culture -- In Vitro Clonal Culture of Human Hematopoietic Progenitor Cells -- High Proliferative Potential Colony-Forming Cells -- Production of Human and Murine Eosinophils In Vitro and Assay for Eosinophil Differentiation Factors -- Flow Sorting for Isolating CFU-E -- Murine Bone Marrow-Derived Macrophages -- Routine Testing of Cell Cultures and Their Products for Mycoplasma Contamination -- Fluorescent In Situ Hybridization (FISH) for DNA Probes in the Interphase and Metaphase Stages of the Cell Cycle -- Cytogenetic Techniques for Human Leukemias -- Visualization of Cell Replication Using Antibody to Proliferating Cell Nuclear Antigen -- Proliferation of Murine Myoblasts as Measured by Bromodeoxyuridine Incorporation -- Analysis of Cell Proliferation Using the Bromodeoxyuridine/Hoechst-Ethidium Bromide Method -- mRNA In Situ Hybridization to In Vitro Cultured Cells -- Transmission and Scanning Electron Microscope Preparation of Whole Cultured Cells -- Adhesion Molecules on Isolated and Cultured Microvascular Endothelial Cells Demonstrated by Immunofluorescence and Immune Electron Microscopy -- Production of Heterologous Proteins Using the Baculovirus/Insect Expression System -- Transfection and Transformation of Human Thyroid Epithelial Cells -- Analyzing Chemotaxis Using the Dunn Direct-Viewing Chamber -- Computer-Assisted Analysis of Single-Cell Behavior.
Keywords: Cell biology; Cell Biology